Local Movie Supply in the German Motion Picture Industry An Industrial Organization Perspective - Kumb, Florian (Springer Fachmedien Wiesbaden : VS, 2018)
Florian Kumb provides a comprehensive review of the current state of the international literature on the motion picture industry and then applies a mix of appropriate quantitative and qualitative research methods in three empirical studies. He enters uncharted research territory examining the effects that major film characteristics cause in the post-theatrical exhibition, he identifies key factors that influence public film funding decisions, and then forecasts the future market development of a European film-financing network. The author shows that the characteristics of local movies, public film funding, and the local film financing network are major reasons for the low international competitiveness of Germany's motion picture industry. Contents Industrial Organization in the Context of the Motion Picture Industry Supply Drivers and the Local Movie Production Subsidization in the German Motion Picture Industry The Influence of Stakeholder Relationships on the Local Film-Financing Network Implications for Local Movie Production in Germany Target Groups Researchers, lecturers, and students in the fields of communications studies Practitioners in the fields of the motion picture industry, in particular film financing in non-U.S. markets The Author Florian Kumb received his doctoral degree under the supervision of Prof. Dr. Reinhard Kunz (University of Bayreuth) and Prof. Dr. Gabriele Siegert (University of Zurich). He has been working in the media industry for German television for more than ten years.